Investigations into pyrolytic behaviour of spent citronella waste: Slow and flash pyrolysis study. (December 2022) - Kaur, Ramandeep; Kumar, Avnish; Biswas, Bijoy; Krishna, Bhavya B.; Bhaskar, Thallada
Graphical abstract: Highlights: Spent citronella biomass is pyrolyzed by slow and flash pyrolysis (Py-GC/MS). Influence of temperature on products yield is revealed. Maximum bio-oil yield of 37.7 wt% is observed at 450 °C with conversion of 71 wt%. Phenolics showed maximum area% (60.05) at optimized temperature. Flash pyrolysis with high heating rate led to maximum area% of carbonyls. Abstract: Slow and flash pyrolysis of spent citronella biomass has been studied at varying temperatures. It is aimed to understand the pyrolytic behavior of spent citronella aromatic biomass with temperatures. Maximum bio-oil yield of 37.7 wt% was obtained with conversion of 71 wt% at 450 °C through slow pyrolysis. GC/MS, 1 H NMR, and FTIR analysis of pyrolytic liquid (bio-oil) was done which indicated various functionalities with maximum area% for phenolics. However, flash pyrolysis at high heating rate of 20 °C/ms resulted into maximum area% for carbonyls at all temperatures. In addition, an increasing trend for phenolics with temperature was also observed. The properties of obtained biochar are analysed by CHNS, FTIR, TOC, XRD, and SEM, which confirmed the significant decomposition of biomass constituents. The characterisation results revealed the potential usage of pyrolytic liquid i.e., bio-oil and pyrolytic residue i.e., biochar for different applications.